Corporate Social Responsibility and Services for People with Disabilities - Raharjo, Santoso Tri; Apsari, Nurliana Cipta; Santoso, Meilanny Budiarti; Humaedi, Sahadi (Asean Social Work Journal, 2024)
Besides making profits, companies have an important duty toward society and the environment. This obligation is manifested in the corporate social responsibility (CSR) program, governed in Indonesia by Law Number 40/2007 on limited liability companies and Law Number 25/2007 on capital investment. By targeting individuals with disabilities, CSR programs can have a significant impact on the lives of those who often face significant challenges. Supporting and empowering individuals with disabilities benefits these individuals and creates a more inclusive and diverse society. By investing in these programs, companies can demonstrate their commitment to social responsibility, improve their reputation, and ultimately contribute to a better world. This article discusses CSR services in Indonesia for people with disabilities using the literature review research. The research found that CSR programs for people with disabilities in Indonesia focus on community services and community empowerment programs. With this program, companies not only provide financial assistance to people with disabilities but also enable people with disabilities through education, training, and empowerment programs. This study found that CSR services for people with disabilities in Indonesia positively impact socioeconomic conditions and contribute to a more inclusive and sustainable development. This study advocates the increasing collaboration with various stakeholders, including the government, NGOs, academics, and the community to ensure the sustainability of the program. The CSR programs are expanded to encompass more rights of people with disabilities.